Facial Flap Complications - Zoumalan, Richard A.; Murakami, Craig S. (Facial Plastic Surgery, 2012)
Knowledge of fundamental concepts can help decrease the chance of complications in plastic surgery. Local flap reconstruction for facial defects has many pitfalls. This article describes common complications in local flap reconstruction of the face and describes strategies that prevent problems.
Keywords: local flap reconstruction; Mohs; complications